Beautiful sacrifice - Lowell, Elizabeth, 1944- (New York : William Morrow, 2012)
A dedicated female archaeologist and a former Immigration and Customs Enforcement Officer must recover priceless South American artifacts that could bring deadly chaos into the world.
Keywords: Women archaeologists -- Fiction; Indians of South America -- Antiquities -- Fiction; Mayas -- Antiquities -- Fiction; South America -- Fiction; Romantic suspense fiction